Soy flour snack bars lower glycaemic response in type 2 diabetes mellitus subjects: A randomised cross-over design. - Nurdin, Naufal Muharam; Navratilova, Hana Fitria; Ekawidyani, Karina Rahmadia; Kurniawan, Mohamad Yulianto (Malaysian Journal of Nutrition, 2022)
Introduction: Low glycaemic snacks may help to improve blood glucose control. However, data on the effect of soybean snack bars on postprandial glucose levels of the diabetic population is scarce. Therefore, the current study aimed to examine the effect of consuming soy flour snack bars on glycaemic response (GR) over a 180-minute period in individuals with diabetes by estimating postprandial glucose levels variation and total area under the curve (AUC). Methods: Nine subjects (age: 54.6±4.0 years; BMI: 25.0±2.5 kg/m2) with type 2 diabetes mellitus (T2DM) diagnoses without complication enrolled in this randomised, open-label, cross-over trial. On three separate sessions, they consumed glucose standard solution, soy flour snack bar (SF), and wheat flour snack bar (WF) containing 25 g of available carbohydrate, respectively. Finger prick capillary method was executed to measure blood glucose levels at 30, 60, 90, 120, 150, 180 minutes after test product ingestion. Results: Overall, significantly lower postprandial glucose levels were observed at 30, 60, 90, and 120 minutes (122.3±17.6, 136.3±24.9, 125.7±25.3, and 107.2±24.1 mg/dL; p<0.001) in those who consumed SF snack bars than WF snack bars (147.9±41.3, 168.0±43.6, 152.6±30.0, and 140.6±33.4 mg/dL). The AUC level after the ingestion of SF snack bar was 2044.8±503.1 mg.min/dL, >20% lower compared to ingestion of WF snack bar (4735.0±666.8 mg.min/dL), p<0.001. These glycaemic control benefits can be explained due to the high fibre and protein content linked to the physicochemical properties of SF. Conclusion: With high nutritional properties, SF snack bar has a low GR and might help control blood glucose in T2DM subjects.